Canada : Financial Sector Assessment Program; Detailed Assessment of the Level of Implementation of the IOSCO Principles and Objectives of Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The regulatory framework for the securities market of Canada exhibits high levels of implementation of the International Organization of Securities Commissions' (IOSCO) Principles. The regulatory framework for most of the areas covered by securities regulation is robust. The general preconditions necessary for the effective regulation of securities markets appear to be in place in Canada. Nevertheless, there are gaps in the regulation and supervision of collective investment schemes (CIS), and enforcement is in need of further improvement, in terms of efficient use of resources.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet